Building categories in interaction linguistic resources at work - Mauri, Caterina, 1981-; Fiorentini, Ilaria; Goria, Eugenio (Studies in language companion series,, 2021)
"This book addresses the topic of linguistic categorization from a novel perspective. While most of the early research has focused on how linguistic systems reflect some pre-existing ways of categorizing experience, the contributions included in this volume seek to understand how linguistic resources of various nature (prosodic cues, affixes, constructions, discourse markers, ...) can be 'put to work' in order to actively build categories in discourse and in interaction, to achieve social goals. This question is addressed in different ways by researchers from different subfields of linguistics, including psycholinguistics, conversation analysis, linguistic typology and discourse pragmatics, and a major point of innovation is represented in fact by the interdisciplinary nature of the volume and in the systematic search for converging evidence"--